Bridging the Paradigm of Restorative Justice: Between Secular Philosophy and Islamic Principles - Majed N Alshaibani (Fakultas Syariah UIN Sultan Aji Muhamamd Idris Samarinda, 2026)
This study addresses how Secular and Islamic principles regulate and operationalize Restorative Justice (RJ) within their respective frameworks. Restorative justice has evolved significantly, influenced by diverse cultural and legal contexts, particularly in indigenous practices that prioritize healing and reconciliation. It evolved from traditional practices emphasizing dialogue and community involvement in resolving conflicts. The study used a comparative legal analysis of the two systems. While restorative justice principles have been formalized in modern legal systems as an alternative to punitive justice, their application varies across Western and Oriental legal frameworks. In Oriental cultures, including Arab and Islamic societies, restorative justice practices involve Shari'ah principles such as Qiṣāṣ, Diyya, and Ṣulḥ that promote dialogue, compensation, and community involvement, and offer rehabilitation rather than punitive action. The study, which used a systematic mapping, revealed that while the secular model relies on state-centric and legal-positivist structures, the Islamic model relies on victim-centric solutions that operate under the administrative patronage of provincial bodies. The study identified that while both systems achieve functional equivalence in conflict resolution, they remain fundamentally distinct in their regulatory infrastructure and their core jurisprudential conceptualization of whether the state or the individual 'owns' the legal conflict.